10m+5+3m=2(m-3)

Simple and best practice solution for 10m+5+3m=2(m-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10m+5+3m=2(m-3) equation:



10m+5+3m=2(m-3)
We move all terms to the left:
10m+5+3m-(2(m-3))=0
We add all the numbers together, and all the variables
13m-(2(m-3))+5=0
We calculate terms in parentheses: -(2(m-3)), so:
2(m-3)
We multiply parentheses
2m-6
Back to the equation:
-(2m-6)
We get rid of parentheses
13m-2m+6+5=0
We add all the numbers together, and all the variables
11m+11=0
We move all terms containing m to the left, all other terms to the right
11m=-11
m=-11/11
m=-1

See similar equations:

| 3f–4f=17 | | e3=1728 | | 3n-5=-8(,6+5n) | | 3.5=(2x÷3)-1 | | 8^x+3=16^2x+1 | | 2(x+1)-1=4x-2(2+x) | | 5x-2-4x+10/5=2/4 | | 5w+9=2w+24 | | 2x+1+6x=3x+51 | | 4(y-10)=6(y+12) | | x(4X-15)=1 | | 3x+5=3x^2+5x | | 6x-2=8x+20 | | 19=-17c | | 36x=18/2 | | 6p-4p=64 | | 6-4/7(14x-12)=8 | | 11=3/4*(3x+12) | | 7.5k+7-6.5k=10 | | C11=3/4*(3x+12) | | 3b+52=b+80 | | 1/2x-8/4=1/2x+18/3 | | N-7-2n=-13 | | 5x(3+4)=40 | | 7=5y–13–y | | 15x-17-14x=-10 | | 7⁸=7⁸.7x | | +2=+2x | | 6-2(x-9)=x+9 | | -3(2x+3)+9x=3x-9 | | 8y+10-7y=3 | | -8.1x-72=3.9x+72 |

Equations solver categories